Intraoperative and postoperative risk factors for anastomotic leakage and pneumonia after esophagectomy for cancer. Issue 1 (21st December 2016) - Goense, L.; van Rossum, P. S. N.; Tromp, M.; Joore, H. C.; van Dijk, D.; Kroese, A. C.; Ruurda, J. P.; van Hillegersberg, R.
SUMMARY: Morbidity and mortality after esophagectomy are often related to anastomotic leakage or pneumonia. This study aimed to assess the relationship of intraoperative and postoperative vital parameters with anastomotic leakage and pneumonia after esophagectomy. Consecutive patients who underwent transthoracic esophagectomy with cervical anastomosis for esophageal cancer from January 2012 to December 2013 were analyzed. Univariable and multivariable logistic regression analyses were used to determine potential associations of hemodynamic and respiratory parameters with anastomotic leakage or pneumonia. From a total of 82 included patients, 19 (23%) developed anastomotic leakage and 31 (38%) experienced pneumonia. The single independent factor associated with an increased risk of anastomotic leakage in multivariable analysis included a lower minimum intraoperative pH (OR 0.85, 95% CI 0.77–0.94). An increased risk of pneumonia was associated with a lower mean arterial pressure (MAP) in the first 12 hours after surgery (OR 0.93, 95% CI 0.86–0.99) and a higher maximum intraoperative pH (OR 1.14, 95% CI 1.02–1.27). Interestingly, no differences were noted for the MAP and inotrope requirement between patients with and without anastomotic leakage. A lower minimum intraoperative pH (below 7.25) is associated with an increased risk of anastomotic leakage after esophagectomy, whereas a lower postoperative average MAP (below 83 mmHg) and a higher intraoperative pH (above 7.34) increase the risk of postoperative pneumonia. These parameters indicate the importance of setting strict perioperative goals to be protected intensively.